Efficacy of Hand Behind Back Mobilization With Movement for Acute Shoulder Pain and Movement Impairment: A Randomized Controlled Trial - Satpute, K.; Bhandari, P.; Hall, Toby (Elsevier Inc, 2015)
The aim of this study was to investigate the effects of hand-behind-back (HBB) Mulligan mobilization with movement (MWM) techniques on acute shoulder pain, impairment, and disability. This double-blind, randomized, controlled trial recruited 44 patients with acute shoulder pain and movement impairment presenting to an Indian general hospital. Participants were allocated to receive either MWM and exercise/hot pack (n = 22) or exercise/hot pack alone (n = 22). The average duration of symptoms was 4.1and 4.7 weeks in the exercise and MWM groups, respectively. The primary outcome was HBB range of motion (ROM). Secondary variables were shoulder internal rotation ROM, pain intensity score, and shoulder disability identified by the shoulder pain and disability index. All variables were evaluated by a blinded assessor before and immediately after 9 treatment sessions over 3 weeks. Paired t tests revealed that both groups demonstrated statistically significant improvements (P < .001) with large effect sizes for all variables. However, for all variables, the MWM-with-exercise group showed significantly greater improvements (P < .05) than the exercise group. Hand-behind-back ROM showed a mean difference of 9.31° (95% confidence interval, 7.38-11.27), favoring greater improvement in the MWM-with-exercise group. In this study, the outcomes of patients with acute shoulder pain and disability receiving shoulder HBB MWM with exercise improved greater than those receiving exercise/hot packs alone.